The Panwaslih Province of Aceh Decision That Conflict With KPU Regulation - Riski Afrial; Husni Husni; Zahratul Idami (Kanun Jurnal Ilmu Hukum, 2021)
The purpose of the research aims to analyse the validity of the decision by Panwaslih Aceh number 001/PS/SN.20/VII/2018 as opposed to article 60 section (1) letter j under KPU regulations number 14 in 2018. KPU regulations do not allow individual prospective candidates to participate in the regional representative board election whose former drug convicts, had committed sexual crimes against children, or had corruption before. the research is normative juridic research using theory and legislation approach. The result of the research showed the moment of decision was made, KPU regulations still applied. The decision of Panwaslih Aceh has already exceeded its own authority as a result of not accommodating KPU regulations. KPU regulations should be changed at first or being said by the supreme court that KPU regulations are contrary to the law. DKPP as electoral management body ethics council was expected to run its function more actively without a complaint first.